1991
DOI: 10.2527/1991.692462x
|View full text |Cite
|
Sign up to set email alerts
|

Roughage sources in beef cattle finishing diets.

Abstract: In four feeding trials with beef steers, corn silage (CS), alfalfa hay (AH), and alfalfa silage (AS) were compared as roughage sources in dry-rolled (DRC); dry whole (DWC); ground, high-moisture (GHMC); and whole, high-moisture corn (WHMC) fattening diets. In processed corn diets (DRC and GHMC), steers fed CS had lower DMI (P less than .05) and feed:gain ratios (P less than .10) than steers fed AS as the roughage source. In a separate trial, greater gains (P less than .10) and lower feed:gain ratios (P less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
5

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
10
1
5
Order By: Relevance
“…Utley et al (1973) reported that 3.7% of the steers fed 80% concentrate and 20% whole peanut hulls had liver abscesses, but when hulls were ground or pelleted, the incidence increased to 56 and 59%, respectively. Cattle fed dry hay tended to have a higher incidence of liver abscesses than cattle fed silage as the roughage source (Mader et al, 1991b(Mader et al, , 1993. Increased feed sorting in diets containing dry roughage (compared to silage) possibly contributes to ruminal acidosis and subsequent liver abscesses.…”
Section: Incidencementioning
confidence: 99%
“…Utley et al (1973) reported that 3.7% of the steers fed 80% concentrate and 20% whole peanut hulls had liver abscesses, but when hulls were ground or pelleted, the incidence increased to 56 and 59%, respectively. Cattle fed dry hay tended to have a higher incidence of liver abscesses than cattle fed silage as the roughage source (Mader et al, 1991b(Mader et al, , 1993. Increased feed sorting in diets containing dry roughage (compared to silage) possibly contributes to ruminal acidosis and subsequent liver abscesses.…”
Section: Incidencementioning
confidence: 99%
“…1995. 73:1888-1900 sources and their effects on feedlot performance (Haskins et al, 1969;McCartor et al, 1972; Moore et al, 1990;Mader et al, 1991). Preston (1991, 1992) demonstrated an economic benefit from reducing the roughage concentration in high-grain feedlot diets during the mid-finishing phase.…”
Section: Introductionmentioning
confidence: 99%
“…Porém, quando as cascas foram moídas ou peletizadas, a incidência aumentou para 56 e 59%, respectivamente. De acordo com Mader et al (1991), bovinos alimentados com dietas contendo forragem seca apresentam uma maior incidência de abscesso hepático quando comparados aos submetidos a dietas contendo silagem como fonte de volumoso, sendo que uma possível justificativa, seria a maior seleção dos alimentos por parte dos animais em dietas contendo forragem seca, o que contribui para o surgimento da acidose ruminal e subsequentemente dos abscessos hepáticos.…”
Section: Incidênciaunclassified
“…Os autores verificaram maior incidência de abscessos hepáticos (11,1%) em bovinos submetidos a dietas com silagem de milho como fonte de volumoso e sem a inclusão de DDGS. Mader et al (1991) relataram maior incidência de abscessos hepáticos em bovinos alimentados com milho grão úmido, em relação ao milho laminado seco. Entretanto, Stock et al (1991) A maior incidência de abscessos hepáticos em bovinos da raça holandesa é justificada pelo maior tempo de alimentação desses animais, e também pelo maior consumo de alimentos quando comparados aos bovinos de corte de peso semelhante (em média 12% maior).…”
Section: Incidênciaunclassified